Os meandros da política hídrica do Comitê de Bacia Hidrográfica do Rio São Francisco : representatividade, efetividade, e formação de hidroterritórios - Torres, Avaní Terezinha Gonçalves (2016)
The water resources management in the world has become, mainly from the twentieth century, an essential element for the establishment of populations and the generation of wealth in the territories, in general. Living with water scarcity, in the Northeast region of Brazil, is part of the formation of the region since its discovery. The most important river of the region is the São Francisco River, also known as the river of "national integration", since its produced wealth was disposed through its riverbed. From the 1970s, the river has been used for the production of energy, more intensively. A displacement of thousands of people occurred as far as the reservoirs have been formed, from the construction of dams by the “Companhia Hidroelétrica do São Francisco (CHESF)”. In the late 1990s, the Law n. 9,443/97 was created, establishing, among other things, territorial water management by basin and consequently its management tools, the granting and the water charge, under the administration of a committee of state representatives, users and organized civil society in each basin. In 2001, the São Francisco River Basin Committee (CBHSF) was created, composed by 62 representative members. In the other hand, the water charge in this basin only occurred from 2010. Part of the funds raised has been used for institutional strengthening of CBHSF, through media campaigns and hydro-environmental projects, mainly in those localities where representatives of CBHSF reside, which reinforce the political image without a significant improvement of water stocks, while the amounts raised should promote the improvement of the quality and quantity of São Francisco River water. Thus, the resources management has not been practiced effectively for not to curb the issuance of grants, even though the river faces a critical scenario of water scarcity. Its waters have been primarily used for energy production usage and irrigation in the irrigated perimeters of agrobusiness. This scenario enhances disputes and resistance between the riparian peasant, irrigators and CHESF, intensifying the disputes between capital and labor by directing the right of the water usage to those in power. These characteristics have set up a territorial formation called by Torres (2007), as “hidroterritório”. The ineffectiveness of CBHSF management increasingly contributes to the formation of those “hidroterritórios”, appointed by space studies of the grants issued to the physiographic regions of Lower-middle and Low São Francisco River, delineation of this research study.